1920 թ. մարտի 23-ի Շուշիի ջարդերը որպես 1915 թ. Հայոց Ցեղասպանության անպատժելիության հետևանք - Բալայան, Վահրամ (ԱրՊՀ հրատ․)
Начиная с конца мая 1918 г. новообразованное мусаватское правительство, всеми возможными и невозможными способами, пыталось завладеть Арцахом. Местные армяне бескомпромиссно боролись сохранить свою государственность и независимость. С января 1919 г. представитель мусаватского правительства Хосров бек Султанов, утверждаясь в Шуши с помощью англичан, пытался реализовать планы Азербайджана по уничтожению армян. В начале 1920 г. Султанов требовал от Национального Совета Карабаха полностью подчиняться Азербайджану. В то же время он приказал мусаватской армии передвигаться и централизироваться в военно-важных пунктах с целью вторжения в Зангезур. Beginning from the end of May in 1918 the newly-proclaimed Azerbaijani government, dominated by the Musavat party, aimed to occupy Artsakh with all possible and impossible means. The Armenians of the land uncompromisingly struggled to keep its statehood and independence. From January 1919 the representative of the Musavat government Khosrov bek Sultanov, with the support of the British, was appointed as a governor in Shushi, tried to carry out anti-Armenian extermination programs. At the beginning of 1920 Sultanov demanded from the National Council of Karabakh fully comply with Azerbaijan. At the same time he ordered musavat army to move and centralize in military significant points with the intent of intruding Zangezur.
Keywords: Արցախ; Հայոց ցեղասպանություն